'Mirror, mirror on the wall': reflecting on, and refracting through, academic development in a pandemic year. Issue 2 (3rd April 2022) - Cunningham, Catriona; Cunningham, Tom
ABSTRACT: Using a creative and playful fairy-tale storyboard approach this paper explores the impact of the pandemic, the move to online and blended learning, and the role academic development can have in the future of learning and teaching. We refract academic staff experiences of teaching during the pandemic through our own experiences as academic developers during this time. We conclude that a balancing act is required to sustain the influence gained in the pandemic whilst retaining the signature pedagogy of playfulness that underpins our work.